2011 North Sulawesi Public Expenditure Analysis : Sub-National Public Financial Management and Development in Bumi Nyiur Melambai - World Bank (World Bank, Jakarta, 2017)
North Sulawesi province is one of the most developed provinces in eastern Indonesia. Far-reaching development has taken place over the past ten years. Presently, North Sulawesi province has the second highest Human Development Index score in Indonesia, and its poverty rate is low in comparison with other provinces. Over the past decade, per capita gross regional domestic product (GRDP) has doubled and sub-national government spending has increased significantly. Nevertheless, there remain various development challenges to address as well as various potential resources and opportunities to pursue. North Sulawesi's performance in regional financial management has been relatively good, but discrepancies remain in the performance and capacity of different work units within each regional government and also between different regional governments in the province. To address challenges, take opportunities, and increase development performance, sub-national governments in North Sulawesi, particularly the provincial government, need to better utilize their fiscal resources. Clearer vision, mission, indicators and development targets must be accompanied by greater efforts to prepare a more directed budget, and to formulate higher quality programs and activities more consistent with planning targets. This report is an effort to assist North Sulawesi's sub-national governments to improve their regional financial management performance, to improve the quality of planning and budgeting, and finally to contribute to local development performance. The report results from strong cooperation between sub-national governments in North Sulawesi province, the Economics Faculty of Sam Ratulangi University, which was supported by CIDA, the Australian Agency for International Development (AusAID) and the World Bank. North Sulawesi Province BAPPEDA (Head of the Regional Development Planning Agency) played an important role in facilitating the preparation of this report. It is expected that this report will benefit North Sulawesi's sub-national governments, sub-national governments elsewhere in Indonesia and the central government by serving as a reference for efforts to improve sub-national financial management performance and the regional development process. Finally, this report can contribute to better and more effective sub-national financial management and governance. Overall, North Sulawesi's strategic sectors (health, education, infrastructure and agriculture) are performing better than in other provinces in eastern Indonesia.